Natural Antioxidants Effect on the Performance of Erythrocytes, Leucocytes, and Hb Levels of Pregnant Mice Exposed to the Plastic - Palupi, Endah Sri; Wibowo, Eko Setio; Puspitasari, IGA. Ayu Ratna; Atang (Biota, 2025)
Plastic is a widely used material with several toxic components, such as free radicals. HDPE plastic is considered safer but requires more attention due to increased usage. Exogen antioxidant is needed to neutralize free radicals. This research aimed to evaluate the effect of natural antioxidants on the performance of erythrocytes, leucocytes, and hemoglobin levels of pregnant mice exposed to plastic compounds. The study used a completely randomized design with six groups and four replicates each. Those groups were aquadest control, plastic chemical compounds (PCC) control, PCC + carrot juice, PCC + orange juice, PCC + purple sweet potato juice, and PCC + mung bean sprouts juice. The PCC was obtained from boiling HDPE plastic, while natural antioxidant juice was from pure sources. Pregnant mice were treated with 0.25 ml of each orally for 21 days, starting from the first gestational day. Blood was collected from a caudal vein. Erythrocytes and leucocytes were counted using a hemocytometer, and Hb levels were measured by the Sahli method. Blood cell morphology was assessed using Giemsa-stained blood smears. Statistical data were analyzed by one-way ANOVA using GraphPad Prism ver.10.0 software, while morphology data were analyzed descriptively. The results showed that PCC and natural antioxidants did not impact the number of erythrocytes, leucocytes, cell morphology, and Hb levels of pregnant mice. However, natural antioxidants may stabilize the erythrocyte total and Hb levels after the treatments are completed.